Sagittal Abdominal Diameter as a Screening Tool in Clinical Research: Cutoffs for Cardiometabolic Risk - U. Risérus; U. de Faire; L. Berglund; M.-L. Hellénius (Hindawi Limited, 2010)
Background. Waist girth and BMI are commonly used as markers of cardiometabolic risk. Accumulating data however suggest that sagittal abdominal diameter (SAD) or "abdominal height" may be a better marker of intra-abdominal adiposity and cardiometabolic risk. We aimed to identify cutoffs for SAD using a cardiometabolic risk score. Design. A population-based cross-sectional study. Methods. In 4032 subjects (1936 men and 2096 women) at age 60, different anthropometric variables (SAD, BMI, waist girth, and waist-to-hip ratio) were measured and cardiometabolic risk score calculated. ROC curves were used to assess cutoffs. Results. Among men SAD showed the strongest correlations to the majority of the individual risk factors; whereas in women SAD was equal to that of waist girth. In the whole sample, the area under the ROC curve was highest for SAD. The optimal SAD cutoff for an elevated cardiometabolic risk score in men was ∼22 cm (95%CI; 21.6 to 22.8) and in women ∼20 cm (95%CI; 19.4 to 20.8). These cutoffs were similar if the Framingham risk score was used. Conclusions. These cutoffs may be used in research and screening to identify "metabolically obese" men who would benefit from lifestyle and pharmacological interventions. These results need to be verified in younger age groups.